2021
DOI: 10.3390/app11125684
|View full text |Cite
|
Sign up to set email alerts
|

Linking Soil Erosion Modeling to Landscape Patterns and Geomorphometry: An Application in Crete, Greece

Abstract: Soil erosion is a severe and continuous environmental problem caused mainly by natural factors, which can be enhanced by anthropogenic activities. The morphological relief with relatively steep slopes, the dense drainage network, and the Mediterranean climate are some of the factors that render the Paleochora region (South Chania, Crete, Greece) particularly prone to soil erosion in cases of intense rainfall events. In this study, we aimed to assess the correlation between soil erosion rates estimated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Several authors proposed C‐values for cultivation operations in olive groves (Moreira Madueño, 1991, 0.4; Kok et al, 1995, 0.54; Giraldez et al, 1989, 0.4 for conventional tillage and 0.45 for no tillage; Gomez et al, 2003, 0.41 for conventional and no tillage). Gómez et al (2021) found a range between 0.12 and 0.50 for the different soil management declared by farmers in Southern Spain, while Brini et al (2021) and Chafai et al (2020) proposed for olive groves generic values of 0.2 and 0.5, respectively. Folly et al (1996) used much higher C‐values (0.7) for olive areas, and López‐Vicente and Navas (2009) even suggested a mean C‐factor of one for olive trees in a catchment of Spanish pre‐Pyrenees.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors proposed C‐values for cultivation operations in olive groves (Moreira Madueño, 1991, 0.4; Kok et al, 1995, 0.54; Giraldez et al, 1989, 0.4 for conventional tillage and 0.45 for no tillage; Gomez et al, 2003, 0.41 for conventional and no tillage). Gómez et al (2021) found a range between 0.12 and 0.50 for the different soil management declared by farmers in Southern Spain, while Brini et al (2021) and Chafai et al (2020) proposed for olive groves generic values of 0.2 and 0.5, respectively. Folly et al (1996) used much higher C‐values (0.7) for olive areas, and López‐Vicente and Navas (2009) even suggested a mean C‐factor of one for olive trees in a catchment of Spanish pre‐Pyrenees.…”
Section: Resultsmentioning
confidence: 99%
“…2021, 11, x FOR PEER REVIEW 4 of 23 simulation for disaster assessment [30]. They detect topographic hazards using GIS models [31] or analyze hazards on slopes in cold regions [32]. In addition, they evaluate and estimate the size of a hazard in high-risk areas, such as roads in hazardous ranges, using spatial data on GIS [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, sub-hourly rainfall rate records from ground-based meteorological stations are rarely available in the Greek territory. Therefore, simplified mathematical equations have been developed in order to estimate rainfall erosivity based on daily or monthly rainfall data derived from gridded satellite and reanalysis products [79][80][81]. The higher the rainfall intensity, the greater the magnitude of soil loss.…”
Section: Rusle Model Descriptionmentioning
confidence: 99%